The CAP study, evaluation of integrated universal and selective prevention strategies for youth alcohol misuse: study protocol of a cluster randomized controlled trial - Newton Nicola C; Teesson Maree; Barrett Emma L; Slade Tim; Conrod Patricia J (BMC Psychiatry, 2012)
Abstract Background Alcohol misuse amongst young people is a serious concern. The need for effective prevention is clear, yet there appear to be few evidenced-based programs that prevent alcohol misuse and none that target both high and low-risk youth. The CAP study addresses this gap by evaluating the efficacy of an integrated approach to alcohol misuse prevention, which combines the effective universal internet-based Climate Schools program with the effective selective personality-targeted Preventure program. This article describes the development and protocol of the CAP study which aims to prevent alcohol misuse and related harms in Australian adolescents. Methods/Design A cluster randomized controlled trial (RCT) is being conducted with Year 8 students aged 13 to 14-years-old from 27 secondary schools in New South Wales and Victoria, Australia. Blocked randomisation was used to assign schools to one of four groups; Climate Schools only, Preventure only, CAP (Climate Schools and Preventure), or Control (alcohol, drug and health education as usual). The primary outcomes of the trial will be the uptake and harmful use of alcohol and alcohol related harms. Secondary outcomes will include alcohol and cannabis related knowledge, cannabis related harms, intentions to use, and mental health symptomatology. All participants will complete assessments on five occasions; baseline; immediately post intervention, and at 12, 24 and 36 months post baseline. Discussion This study protocol presents the design and current implementation of a cluster RCT to evaluate the efficacy of the CAP study; an integrated universal and selective approach to prevent alcohol use and related harms among adolescents. Compared to students who receive the stand-alone universal Climate Schools program or alcohol and drug education as usual (Controls), we expect the students who receive the CAP intervention to have significantly less uptake of alcohol use, a reduction in average alcohol consumption, a reduction in frequency of binge drinking, and a reduction in alcohol related harms. Trial registration This trial is registered with the Australian and New Zealand Clinical Trials registry, ACTRN12612000026820.